Smart contact center: the new customer service model - Silva, Grazyely Larios (2018)
This study aims to analyze the problems and causes of dissatisfaction reasons consumers with the services offered by organizations and possible solutions of Information Technology (IT) can generate improvements in processes of Customer Service (CS) and therefore increase customer satisfaction. For this, the paper presents the concept of Customer Relationship Management (CRM), Omnichannel, Call and Contact Centers. For demonstrating the benefits of deploying an intelligent solution in the contact center to conduct a data analysis for diagnosis of consumer customer perspective on customer service and what are the impacts that generates satisfaction to an organization.